(untitled) (Journal of Parents and Teachers, 1996)
The importance of the curriculum and pedagogical objectives in education is addressed, highlighting the need to consolidate hypotheses and evaluation criteria. Alignment with official curricular objectives and the planning of activities to improve teaching are emphasized. In addition, administrative decisions related to education are mentioned.